“Para João Antônio, pela força aos novos e à literatura”: dedicatórias como elementos constituintes de um projeto literário - Moraes, Renata Ribeiro de [UNESP] (2014)
The present research analyses the contents of the dedications sent to João Antonio (1937-1996) by some renowned writers who had contact with the author from São Paulo. Such dedications appear as constituent elements of the story writer´s literary project. From the collection of dedicated works, sent between the decades of 1960 and 1990, we have selected some paratexts. They approach themes like the Brazilian editorial market at the mentioned time, João Antônio´s literary affiliations, his professionalization as a writer and others, that show the affection, respect and admiration links towards the addressee. Authors like Jorge Amado, Caio Porfirio Carneiro and Cassiano Nunes, with their respective dedications bring to discussion the themes above referred to. The dedications sent by Clarice Lispector, Cleonice Rainho, Nélida Piñon and Nelly Novaes Coelho, on the other hand, show the position of Brazilian female authors in face of the national literary production and whose creations show the ways they inserted themselves into a universe remarkably masculine, having in view the greater number of male authors published. From the context of authors who sent dedications, our research will attain to the paratexts whose authors were contemporary to João Antônio, for our goal is to demonstrate in what degree the dedications can be seen as constituent elements of this story writer´s literary project formation